2001
DOI: 10.1002/app.1313
|View full text |Cite
|
Sign up to set email alerts
|

Sorption properties of poly(styrene‐co‐divinylbenzene) amine functionalized weak resin

Abstract: ABSTRACT:The poly(styrene-co-divinylbenzene) amine functionalized weak resin was studied as adsorbent of heavy metal ions from an aqueous solution by using the Batch equilibrium procedure. The resin adsorbed Hg(II) 56% (0.56 mEq/g) at pH 2, and 45% (1.13 mEq/g) of U(VI), 38% (0.36 mEq/g) of Pb(II) at pH 5 from an aqueous solution containing 1 g/L of each metal ion. It did not adsorb Cd(II), Zn(II). The equilibrium time was achieved during the first hour. The maximum load capacity for Hg(II) was 0.8 mEq/g (75 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The development of high‐performance adsorbents for removing heavy metal ions from wastewater is considered a research priority in environmental science 1–20…”
Section: Introductionmentioning
confidence: 99%
“…The development of high‐performance adsorbents for removing heavy metal ions from wastewater is considered a research priority in environmental science 1–20…”
Section: Introductionmentioning
confidence: 99%
“…The development of high-performance adsorbents for removing heavy metal ions from wastewater is considered a research priority in the environmental field. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Chelating resins have been successfully used for enriching and separating some metal ions from aqueous solutions. They are very useful because they have a higher selectivity and larger adsorbing capacities than those of other adsorbents (e.g., activated carbons and metal oxides) and they are also easily eluted and regenerated.…”
Section: Introductionmentioning
confidence: 99%
“…Metal ions are nonbiodegradable in nature; their intake at a certain level is toxic 1. Attempts have therefore been made to incorporate a vast number of chelating groups into a polymer network 2–8. Of various common methods to prepare such chelating resins, by far the most common technique is the chemical modification of crosslinked polymers.…”
Section: Introductionmentioning
confidence: 99%
“…10 -12 In recent studies on complexing polymers in our laboratory, we reported on the synthesis of structures bearing amide, amine, ammonium, and carboxylic groups obtained by radical polymerization. [13][14][15][16][17][18] Complexing properties of these structures have been investigated by the batch equilibrium procedure to study their behavior in respect to different metal ions. We have now extended these investigations to the synthesis of insoluble polymers containing carboxylic, sulfonic, and imidazole groups.…”
Section: Introductionmentioning
confidence: 99%